The Effect of Using Sustainable Materials on the Performance-Related Properties of Asphalt Concrete Mixture - Albayati, Amjad H.; Turkey, Waleed Arrak (Salehan Institute of Higher Education, 2019)
Sustainability is very important in this world at this time. One of the best materials used for sustainability in asphalt concrete pavements is the warm mix asphalt (WMA) as well as the reclaimed asphalt pavement (RAP). WMA technology has the ability to reduce production temperature to reduce the fuel usage and emissions. RAP is the old concrete asphalt mixture that is out of service and using it again leads to preservation of the virgin material. This search studied the viability of using WMA with different percentages of RAP (10%, 30%, and 50%) and compared them with control hot mix asphalt (HMA) and WMA. The Marshall properties, Tensile strength ratio (TSR), rut depth and fatigue life were determined in this work. The results showed that the tensile strength ratio (TSR) for HMA was better than that for WMA by 6%, rut depth for HMA was (4.37 mm) lower than that for WMA was (6.5mm), better fatigue life was obtained for WMA was (700 cycle) as compared to HMA was (500 cycle). In case of WMA with RAP (WMA-RAP), when the percentage of RAP increased with WMA, the moisture damage resistance improved by 2.5%, 13.3% and 15.4% for G1, G3 and G5 respectively, also the rutting resistance improved by 34.6%, 48% and 62.3% for G1, G3 and G5 respectively, but deteriorated of fatigue life by 45.8%, 74% and 88.5% for G1, G3 and G5 respectively.